The influence of local cosmetics video-sharing review on female dailynetwork youtube channel towards viewers purchase intention - Fathiha, Zhalysha Yoanda; Aprilianty, Fitri (Journal of Business and Management, 2020)
Abstract. The competition of cosmetics industry in Indonesia are getting fierce since there are so many brands that emerges so the effort to lead the market must be harder. In order to survive this fierce competition, nowadays local cosmetic marketers market their product in many ways and online channel is one of the way uses to deliver their marketing message. FemaleDailyNetwork YouTube channel is an account that provides various information and review about cosmetic products that have launched in Indonesia. This research aims to identify the factors that influence viewers purchase intention of local cosmetic and analyze the decision process of viewers to buy local cosmetic products upon the value of communication perceived from watching Video-Sharing Review onFemaleDailyNetwork Youtube Channel. This study explores factors (number of views, likes,comment, and replies, perceived credibility, perceived video characteristics, perceived usefulness, attitude toward purchase, and purchase intention). The data was collected through semi-structured interview and survey then analyzed by open coding and CB-SEM. The result indicates that perceived video characteristics, perceived usefulness, and attitude toward purchase are influencing customers’ purchase decision. The finding of this research is expected to improve FemaleDailyNetwork YouTube channel as the marketing strategy for local cosmetics products in Indonesia. Keywords: FemaleDailyNetwork, Local Cosmetics, Purchase Intention, Video-sharing review, YouTube